Factors that contribute to the work-family conflict in Permodalan Nasional Berhad (PNB) - Azizi Yahaya; Peter Voo Su Kiong; Balan Rathakrishnan; Ismail Maakip; Baharudin Mohd Arus; Malai Yunus Malai Yusuf; Sonny anak Jumpo; Nor Hasnul Hamdani; Suraya Fadilah Ramli; Koay, Ting Yin; Nurul Diyana Mohamed Noor (2019)
Work–family conflict is a type of inter-role conflict that occurs as a result of incompatible role pressures from the work and family domains. Work role characteristics that are associated with work demands refer to pressure arising from excessive workload and time pressures. The purpose of this research is to identify the factors that contribute to the work-family conflict. There are three factors that researchers focus which are role overload, management support and also gender role orientation. The results of the study implied that work-family conflict as an important concern for individuals and organizations because of its negative consequences leading to reduced job performance as well as family satisfaction and hence reduced life satisfaction